NK Cell Effector Functions Regulation by Modulating nTreg Cell Population During Progressive Growth of Dalton's Lymphoma in Mice. (2nd January 2018) - Tomar, Munendra Singh; Kumar, Sanjay; Kumar, Sanjay; Gautam, Pramod Kumar; Singh, Rishi Kant; Verma, Praveen Kumar; Singh, Surya Pratap; Acharya, Arbind
ABSTRACT: Natural killer (NK) cells are large granular lymphocytes of the innate immune system and play a pivotal role against virus-infected cells, microbial pathogens, and tumor cells. NK cells secrete several cytokine, s but IFN-γ secreted by NK cells play a vital role in the activation of the innate and adaptive immune systems. But during any infection or tumor burden, functional activity of NK cells is downregulated significantly by nTreg cells. It is also found that during tumor progression, the number of nTreg cells increases as a result; it effectively suppresses the antitumor activity of NK cells. Therefore, in the present investigation, we intend to examine the mechanism of downregulation of antitumor immune response mediated by NK cells. We observed increased NK cell population at an early stage of Dalton's lymphoma (DL) growth, while at late stage, NK cell numbers were decreased. The NK cell functional activity was govern by high level of IFN-γ measurement during tumor progression. The FoxP3 + CD25 + CD4 + T regulatory cell population was found to be continuously increased with high-level expression of FoxP3 during DL growth. The rapid increase in the number of Treg cells during DL progression may be due to high level of the FoxP3 transcription factor. The tumor microenvironment of DL cell progression has highly deleterious effect on NK cells after massive growth of tumor burden in BALB/c mice. This result also indicates that NK cell proliferation, activation, and accumulation are under the control of regulatory T cells.